2016
DOI: 10.1371/journal.pone.0167094
|View full text |Cite
|
Sign up to set email alerts
|

AS1411-Induced Growth Inhibition of Glioma Cells by Up-Regulation of p53 and Down-Regulation of Bcl-2 and Akt1 via Nucleolin

Abstract: AS1411 binds nucleolin (NCL) and is the first oligodeoxynucleotide aptamer to reach phase I and II clinical trials for the treatment of several cancers. However, the mechanisms by which AS1411 targets and kills glioma cells and tissues remain unclear. Here we report that AS1411 induces cell apoptosis and cycle arrest, and inhibits cell viability by up-regulation of p53 and down-regulation of Bcl-2 and Akt1 in human glioma cells. NCL was overexpressed in both nucleus and cytoplasm in human glioma U87, U251 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…It has also been associated with poor prognosis for a variety of types of cancer (24,25). For example, nucleolin inhibits P53 and enhances Bcl-2 and protein kinase B (Akt) expression to promote the proliferation of human glioma cells (26). Other studies demonstrated that phosphorylation of nucleolin may be associated with cancer metastasis and cell proliferation (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been associated with poor prognosis for a variety of types of cancer (24,25). For example, nucleolin inhibits P53 and enhances Bcl-2 and protein kinase B (Akt) expression to promote the proliferation of human glioma cells (26). Other studies demonstrated that phosphorylation of nucleolin may be associated with cancer metastasis and cell proliferation (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…We further observed that the TDP-43-dependent activation of apoptotic cell death in human cells was signi cantly reduced by NCL co-expression ( Fig. 9), suggesting that NCL could suppress TDP-43 toxicity also by directly acting as an antiapoptotic factor, in light of its reported ability to stabilize the mRNA of the Bcl-2 anti-apoptotic factor [95][96][97], and to modulate p53 signalling at multiple levels [98][99][100]. We indeed observed that NCL overexpression was able to rescue the normal Bcl-2 levels in TDP-43 overexpressing HEK293T cells, without, however, affecting Bcl-2 expression in cells expressing endogenous TDP-43 amounts.…”
Section: Discussionmentioning
confidence: 75%
“…They have been investigated for a wide range of applications including imaging [133] and cancer therapeutics [131]. For example, AS1411, a Nucleolin specific aptamer, was the first oligodeoxynucleotide to reach phase I and II clinical trials for the treatment of cancers [134], including acute myeloid leukemia (NCT01034410) and renal cell carcinoma (NCT00740441). Additionally, Ye Cheng et al demonstrated in vitro and in vivo , the therapeutic potential of this aptamer for GBM.…”
Section: Assessing Rnai Delivery For Gbm Treatmentmentioning
confidence: 99%
“…Additionally, Ye Cheng et al demonstrated in vitro and in vivo , the therapeutic potential of this aptamer for GBM. Their results showed that treating U87-MG, U251, and SHG44 GBM cells with AS1411 reduced cell migration [134]. Local administration of AS1411 led to decreased tumor growth and prolonged overall survival in a subcutaneous U87-MG xenograft mouse model [134].…”
Section: Assessing Rnai Delivery For Gbm Treatmentmentioning
confidence: 99%
See 1 more Smart Citation